Estimasi Simpanan Karbon Atas Permukaan Di Kawasan Wisata Alam Pulau Tareba, Kota Ternate: Estimation Of Above Ground Carbon Storage In The Pull Tareba Natural Tourism Area, Ternate City - Fatima Ahz Zhahra; Andy Kurniawan; Reyna Ashari (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2026)
Carbon is an essential element and plays a significant role in controlling climate change. One form of storage is found in aboveground biomass. This research was conducted in the Pulo Tareba Natural Tourism Area, Takome Village, West Ternate District, with an area of approximately 3 hectares. Pulo Tareba is part of the Community Forest, the Tolire Gam Jaha Forest Farmer Group, which is managed by the Ternate-Tidore Forest Management Unit. To date, quantitative data on carbon storage is not available, so this study aims to determine the potential for aboveground carbon storage, such as in living trees, dead trees, litter, and understory vegetation in the area. Data collection was carried out using the plot method in accordance with SNI 7724:2019, with plot sizes of 20 × 20 m for live and dead trees, and 2 × 2 m for litter and undergrowth. Data analysis was performed using allometric calculations from Kettering et al. (2001) and SNI 7724:2019. The research results show that the total biomass in the Pulo Tareba Natural Tourism Area reaches 399.252 tons/ha, with a total carbon storage of 187.651 tons/ha. Carbon storage based on vegetation components shows that trees are the largest contributor with a value of 94.86 tons/ha, followed by litter at 77.21 tons/ha, undergrowth at 15.58 tons/ha, and dead trees (necromass) at 0.0009 tons/ha. The results of this research can be used as a consideration for the Ternate-Tidore Forest Management Unit (KPH) and area managers in designing conservation area preservation strategies. Keywords: Allometric, Biomass, Pulo Tareba, Carbon Storage, SNI.